Distributed internal strain measurement during composite manufacturing using optical fibre sensors. (4th December 2015) - Sánchez, Daniel Martínez; Gresil, Matthieu; Soutis, Constantinos
Abstract: After manufacturing a composite laminate, it is expected to store residual stresses that might affect the mechanical response of the plate. An optical fibre sensor was embedded in an epoxy carbon fibre panel, measuring the development of residual strain by monitoring in-situ and in real-time the manufacturing process, from the resin infusion to the curing cycle, and the changes experienced within. An optical sensor interrogator detects and measures changes in strain and temperature along the optical fibre length with high precision and accuracy, making it possible to obtain a full strain/temperature profile. Data acquired from the embedded sensor led to track and characterize the strain profile at every stage of the manufacturing process. This work showed that the infusion stage is highly related to the residual strain after the curing process. Moreover, the residual strain is 40% higher near the edge compared to the mean value measured in the laminate.